2011
DOI: 10.1097/wnr.0b013e328345ac22
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of the human STON2 gene with schizophrenia

Abstract: Synaptic hypothesis of schizophrenia suggests that alterations of synaptic transmission and neuronal connectivity might be core feature of schizophrenia. STON2 participates in synaptic vesicle protein recognition and neural endocytosis. To explore the association of STON2 with schizophrenia, 11 single nucleotide polymorphisms (SNPs) were examined in 768 Chinese Han schizophrenia cases and 1347 Chinese Han controls. The results showed that three SNPs had strong association with schizophrenia, two exonic SNPs (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Whether the reduced levels of Syt1 observed in SV2A/B/Stn2 TKO neurons are indeed the result of facilitated Syt1 degradation will need to be addressed in future studies. Given the putative genetic association of Stn2 with neuropsychiatric disorders including schizophrenia and autism spectrum disorders (24, 39, 40) and the role of SV2A in late onset Alzheimer’s disease (41) and as a major target of the antiepileptic drug levetiracetam (42, 43), our results may also be of relevance for the diagnosis and treatment of neurological disorders in humans.…”
Section: Discussionmentioning
confidence: 87%
“…Whether the reduced levels of Syt1 observed in SV2A/B/Stn2 TKO neurons are indeed the result of facilitated Syt1 degradation will need to be addressed in future studies. Given the putative genetic association of Stn2 with neuropsychiatric disorders including schizophrenia and autism spectrum disorders (24, 39, 40) and the role of SV2A in late onset Alzheimer’s disease (41) and as a major target of the antiepileptic drug levetiracetam (42, 43), our results may also be of relevance for the diagnosis and treatment of neurological disorders in humans.…”
Section: Discussionmentioning
confidence: 87%
“…These alterations resemble arousal seeking and impulsivity observed in patients suffering from Tourette syndrome (35) or schizophrenia (36). Recent data from human genetics have indeed revealed a possible association of Stn2 with such neuropsychiatric disorders including schizophrenia and autism-spectrum disorders (37,38). Hence, the work reported here could serve as a starting point for the dissection of the molecular mechanisms underlying these neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, loss of Stn2 causes increased locomotion-and exploration-related behaviors in mice. This phenotype resembles arousal seeking and impulsivity observed in patients suffering from Tourette syndrome (35) or schizophrenia (36), which are neuropsychiatric disorders linked to mutations in Stn2 in humans (37,38).…”
Section: Resultsmentioning
confidence: 99%
“…Pro307Ser polymorphism is adjacent to an Asn-Pro-Phe or NPF motif, which may mediate the interaction of stonin2 with intersectin and Eps15, as well as the haplotype C-C of Ser307Pro and Ala851Ser polymorphisms (Pro307-Ala851), which affects the stonin2 function that mediates the etiopathogenesis of schizophrenia [33]. In the present study, no significant difference was found in the frequencies of both Ser307Pro and Ala851Ser polymorphisms in STON2 gene, either genotype-wise or allele-wise, between patients with schizophrenia and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Transport, fusion, and recycling of SV affected the normal synaptic function and were critical in maintaining the ability of the synapse to release a neurotransmitter based on sustained stimulation [30], [31], [32]. Two exonic single-nucleotide polymorphisms (SNPs) of the STON2 gene were associated with schizophrenia in a Chinese population [33]. The present study aimed to investigate the relationship between the genetic of the STON2 gene and the cortical surface area in patients with schizophrenia and healthy controls.…”
Section: Introductionmentioning
confidence: 96%